Communicating Process Architectures 2002 : WoTUG-25 : Proceedings of the 25th WoTUG Technical Meeting, 15-18 September 2002, University of Reading, United Kingdom - Pascoe, James (Concurrent systems engineering series, 2002)
The WoTUG series of conferences are a major forum for the presentation of state-of-the-art ideas on concurrency and communication. This book continues this trend, with these proceedings containing a number of papers that discuss a wide range of issues fundamental to the future of concurrency. This book combines papers from researchers and practitioners from many disciplines. Topics covered include: theory, such as development to Hoare's Communicating Sequential Processes; hardware and real-time systems; software architecture and design; and applications.